Experiment on the flammability variation of micron-sized aluminum powder depending on combustion environment for burning of aluminum-diluted oxygen. (January 2021) - Ko, Taeho; Ki, Wando; Lee, Kookjin; Lee, Hyungsuk; Noh, Kwanyoung; Yoon, Woongsup; Song, Soonho
Abstract: Experimental research was conducted to study the combustion characteristics of clouds composed of micrometer-sized aluminum particles with an oxidizer blend of oxygen and superheated steam. Both ignition and combustion of an aluminum particle are difficult because it is enveloped by an oxide layer that has a high melting point (above 2300 K). To overcome the problem, we induced a particular shape of the combustor that can keep a stable flame of aluminum dust clouds at a lower feeding-rate. The combustion characteristics were examined using a system applied combustor involving a variety of parameters affecting the burning of the dust clouds. Based on these attempts, the aluminum dust clouds had an upper flammability limit above the equivalence ratio (Ф) 1.9 for oxygen diluted by air. Varying the lower limit of flammability, we found, crucially, that the feeding-rate and velocity of the particles are more effective than the equivalence ratio or combustor length. Furthermore, we could confirm the changing of the lower limit from 0.3 to 0.26 because the steam was additionally fed in the combustion of aluminum-oxygen. Highlights: Designed Combustor that Al dust can be terminated the burning without depositing. Variation of the lower limit of flammability depending on Al dust feeding conditions. Confirming the changing of a lower limit owing to feeding steam in Al–O2 flame.